Scientific opinion on an application for renewal of authorisation for continued marketing of maize 1507 and derived food and feed submitted under Articles 11 and 23 of Regulation (EC) No 1829/2003 by Pioneer Overseas Corporation and Dow AgroSciences LLC. (12th January 2017) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: Following the submission of application EFSA‐GMO‐RX‐001 under Regulation (EC) No 1829/2003 from Pioneer Overseas Corporation and Dow Agrosciences LLC, the Panel on Genetically Modified Organisms of the European Food Safety Authority (GMO Panel) was asked to deliver a scientific risk assessment on the data submitted in the frame of a renewal of authorisation application of the insect‐resistant and herbicide‐tolerant genetically modified (GM) maize 1507. The data package received in the frame of this renewal application contained post‐market environmental monitoring reports, a systematic search and evaluation of literature, an updated bioinformatics analysis and additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed this data package for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the frame of the original application. Under the assumption that the DNA sequence of the event in maize 1507 considered for renewal is identical to the corrected sequence of the originally assessed event, the GMO Panel concludes that no new hazards or modified exposure and no new scientific uncertainties were identified for the application for renewal that would change the conclusions of the original risk assessment on maize 1507 (EFSA, 2005b, 2009 ).